Raising Resilient Children Parents and Teachers Working in Partnership to Empower the Children in Our Lives - Cleeve, Kelly (Peter Lang Inc., International Academic Publishers, 2020)
Raising Resilient Children: Parents and Teachers Working in Partnership to Empower the Children in Our Lives provides tips that you can use in your daily interactions with children to create an environment in which children will thrive. We all want to raise good children, children who are kind, smart and well prepared to become adults in an increasingly complicated world. The best predictor of a child's future success is their level of resilience, their ability to overcome challenge. Yet, this skill set has been largely ignored in the past. Teachers and parents are the greatest influences on a child's mindset and if we work together to foster resilience in our children, their potential for happiness and success increases exponentially. If you are a teacher, looking for practical classroom tips to increase emotional intelligence and self-regulation, this book is for you. If you are a parent, in search of ideas for how to elevate your child's mental well-being, this book is for you too.
Keywords: výchova dítěte; vývoj dítěte; psychická odolnost; child rearing; child development; psychic resistance; elektronické knihy; electronic books